Metro Revealed Building Windows 8 Apps with XAML and C# - Freeman, Adam.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
This 88-page primer unveils the key features of Microsoft's eagerly anticipated Windows 8 operating system. Windows 8 contains the revolutionary Metro application framework for building dynamic and responsive touch-enabled applications that target both desktops and mobile devices. With the official release of Windows 8 looming ever closer, experienced author Adam Freeman invites you to take a crash course in Metro development. Using XAML and C#, he ensures you understand the changes that are being made to Windows development practices and puts you on the right course to creating innovative and elegant applications for this latest evolution of the world$1 (Bs most successful operating system.s
Keywords: Computer science; Computer Science; Computer Science, general